EP1203 Cytoreductive surgery for tubo-ovarian carcinoma - a study of MDT decision-making for primary vs NACT-interval surgery. (1st November 2019) - Daly, R; Shahabuddin, Y; Thompson, C; Gleeson, N
Abstract : Introduction/Background: Primary debulking/cytoreductive surgery (PDS) is considered the optimal approach in the management of tubo-ovarian carcinoma (TOC). Neoadjuvant chemotherapy (NACT) with interval cytoreductive surgery (IDS) is not considered inferior to PDS. The aim of this study was to analyse the multidisciplinary team (MDT) decision-making process in assigning patients to PDS or NACT at this Irish tertiary gynaecological oncology centre. Methodology: This is an observational retrospective study on consecutive patients with invasive serous and non-serous TOC, presenting from 1st January to 31st December 2018. Borderline, non-epithelial and low grade tumours were excluded. Patient demographics, staging, histology and pre-treatment biochemistry and tumour markers were reviewed. Treatment modalities (PDS, NACT-IDS, chemotherapy alone) were documented. Results: Of 88 patients assessed by MDT, 31 were excluded. 41 patients had radiological stage III (61%, n=25) or IV disease (39%, n=16). 90% (n=37) were high-grade serous. 30 patients (52.6%) underwent PDS. 44.6% (n=14) were radiological stage III 14 (46.6%) and 3.33% Stage IV (n=1). Median age was 55.6 years and median Ca125 was 929. Complete cytoreduction was achieved in 27 patients (90%). 24 patients underwent primary chemotherapy. 45.9% (n=11) were radiological stage III and 54.1% (n=13) were Stage IV. Median age was 64 years and median Ca125 was 1902. 13 patients did not progress to IDS due to suboptimal chemotherapy response (n=5) and poor surgical candidacy due to comorbidities (n=4). Conclusion: High grade serous was the most common histology. Achieving complete cytoreduction in the majority of the PDS group suggests MDT decision was correct. Patients selected for chemotherapy were more likely to have stage IV disease, higher age and Ca125. Half of patients receiving primary chemotherapy never progressed to surgery. Their poor baseline performance status may also be as important as chemo-resistance in that outcome. Robust comparisons of outcomes for PDS vs NACT-IDS need to pay close attention to patient stratification. Disclosure: Nothing to disclose